Trajectories of psychological distress for Australian fathers parenting a child on the autism spectrum: Evidence from early childhood to adolescence - Seymour, Monique (My University, 2024)
Most research on the mental health of fathers with children on the autism spectrum has been cross-sectional. Little is currently known about the trajectories of fathers’ mental health across their parenting journey. Using longitudinal latent class analysis, this study aimed to: (1) report on the estimates of fathers’ psychological distress across six timepoints, from when their children were aged 4–14 years; (2) identify classes of fathers as defined by their trajectory of distress over time; and (3) identify early psychosocial risk factors associated with the identified trajectories of psychological distress. Participants were 281 fathers of children on the autism spectrum who participated in the Longitudinal Study of Australian Children. Longitudinal latent profile analysis across the six timepoints of data identified a two-class model best fit the data, with profiles reflecting minimal distress (n = 236, 84%) and elevated and increasing distress (n = 45, 16%). Regression analysis revealed ongoing medical conditions and heightened interparental conflict as significant predictors to sustained psychological distress. Findings highlight that psychological distress persists for a substantial portion of fathers throughout their child’s development. Strengthening fathers’ physical health and enhancing the couple relationship are potential avenues for positively impacting fathers’ long-term mental health.
Autism
Keywords: Childhood and child development; Families and relationships